PENGARUH FASHION ORIENTATION DAN DEPARTMENT STORE PERSONALITY TERHADAP DEPARTMENT STORE PATRONAGE INTENTION DENGAN NILAI BELANJA SEBAGAI VARIABEL MEDIASI DI MATAHARI DEPARTMENT STORE BANDA ACEH - Mulyana, Syafruddin Chan (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This study aims to determine the influence of fashion orientation and department store personality towards department store patronage intention, with shopping value as the mediating variable. The samples used in this study were 120 respondents who had visited and recommended Matahari Department Store. The sampling technique used was Purposive Sampling. The Analysis of Moment Structure (AMOS) was used as the method of analysis to determine the effect of the variables involved. The results of this study showed that fashion orientation was not influential towards department store patronage intention, and department store personality significantly influenced department store patronage intention. In addition, the results showed that the shopping value variable mediated fashion orientation with the value of direct influence as much as 0,330 greater than indirect influence which was as much as 0,206, and shopping value variable mediated department store personality with the value of direct influence as much as 0,559 and the Indirect influence as much as 0.350, so in this research, fashion orientation and department store personality variables partially affected the department store patronage intention.Keywords: Fashion Orientation, Department Store Personality, Department Store Patronage Intention, Shopping Value